Powerful knowledge, myth or reality? Four necessary conditions if knowledge is to be associated with power and social justice (UCL Press, 2020)
Can knowledge be powerful and, if so, what forms do knowledge and power take? The view of some social realist curriculum theorists that power exists in academic theories although not in everyday understanding is questioned. Power is taken to exist through social positions, and to involve control over resources, decisions and change. Critical realist analysis suggests that four conditions are necessary if knowledge is to be associated with power: the known, the knowers, the social contexts and the practical application of knowledge. Questions are considered about how today's schools can promote learning and social justice.